Isolated primary craniopharyngioma of the fourth ventricle: a rare case report and literature update - Chen, Ligang; Yang, Xinyu; Liu, Xuantong; Wang, Geyu; Li, Xinning; Sun, Xiaoyu; Feng, Sizhe; Liang, Guobiao (Frontiers in Oncology, 2026)
BackgroundCraniopharyngiomas usually occur in the saddle and suprasellar regions, and primary cases occurring in the fourth ventricle are extremely rare, with only eight definite cases reported in the English literature. In this article, we present the ninth case of primary craniopharyngioma of the fourth ventricle.Case descriptionThe patient was a 51-year-old man who complained of progressive occipital headache, unsteady gait and vomiting. Imaging showed a cystic occupying lesion in the fourth ventricle with calcification of the cystic wall, which compressed the aqueduct and led to obstructive hydrocephalus. Images of the saddle and suprasaddle regions were completely normal, and there was no history of surgery. The patient underwent suboccipital median approach, cerebellar hyaloid surgery, and total resection of the tumor. Pathology suggested an adamantinomatous type craniopharyngioma with positive β-catenin nuclei. Postoperative recovery was good, and no recurrence was seen at 12-month follow-up.ConclusionThe case in this article is an isolated primary fourth ventricle craniopharyngioma with no history of saddle region extension or surgery. Its clinical presentation and pathologic features support an embryologic mechanism of residual development of Rathke’s capsule. It is recommended that craniopharyngiomas be included in the differential diagnosis when evaluating locoregional lesions in the posterior cranial fossa, especially if the imaging manifestations are cystic or contain calcifications.